SAHALA: KEPEMIMPINAN PEREMPUAN DALAM KONTEKS MASYARAKAT BATAK DAN ALKITAB - Riris Johanna Siagian (VISIO DEI: JURNAL TEOLOGI KRISTEN, 2019)
This study is an effort to explore a more concrete and holistic understanding related to the existence and woman's role in Batak society. In reality, Batak has several terms which refer to the strong existence of women in Batak society. However, since the lineage is drawn from the male line, as is the case in a patriarchal culture, the strategic roles of women themselves often become neglected. This study conducted a constructive critical study to position women’s leadership in the context of the Batak community. It began by describing the actual conditions of women in the context of the Batak community. Furthermore, a constructive critical study was carried out by looking at religious literature and myth. The use of myths as study material is usually done in the study of the Sciences of Religions because people believe that myths contain teachings about the moral of a society, which are accepted and lived as teaching in daily life. Through that, things can also be found to be learning for the future. The study of the Sciences of Religion also uses the Sociology of Religion to discuss humanity and religion. Theological reflection on specific texts in the Bible is carried out with a new perspective. This way is done to raise the strength of women. Of course, this study has already been finished by a deep and prolonged study, so what is presented here is the result of the researcher's recommendations only.